Aplikasi Go Tour Sekitar Tugu Yogyakarta Berbasis Augmented Reality - Putri, Revanda Silva Astianto; Rahmawati, Yunianita; Busono, Suhendro; Eviyanti, Ade (Jurnal Teknologi dan Manajemen Informatika, 2023)
The Covid pandemic has impacted the tourism industry in Central Java Province, resulting in a decrease in the number of tourists. This research aims to create an application as an information media using Augmented Reality technology and developed through SketchUp, combining text, audio, and images. This application serves as an information source for the Tugu Yogyakarta tourist attraction and its surrounding areas in Central Java. Additionally, it also serves as an alternative to introduce tourist attractions to both the local and non-local communities in and outside of Central Java Province. The application utilizes the Marker Based Tracking method. The research output is an Augmented Reality application for information media that displays 4 tourist attractions, with audio-based information for each attraction. The testing scenario is conducted using the black box testing method (testing the system or its features). Based on the response evaluation, it can be concluded that this information media is considered suitable with a percentage of 94.8%. Therefore, this application can be used as an effective information media.